Structure and properties dependence of hydrogenated carbon films on conditions of synthesis at Ar+CH4+H2 plasma - Ryaguzov, A.P.; Alpysbayeva, B.E.; Nemkayeva, R.R.; Aliaskarov, R.K.; Mamyrbayeva, D.M.; Yukhnovets, O.I. (Publishing House of the KarSU named after E.A.Buketov, 2016)
In this paper we perform study of amorphous hydrogenated a-C:H films, obtained by method of magnetron DC ion-plasma sputtering of high-pure graphite target in Ar+CH4+H2 gas mixture. Growth of a-C:H films occurs at sufficiently non-equilibrium conditions, that differ not only by the main thermo dynamical parameters, but also physical-chemical processes of atoms condensation on the substrate. In order to reveal the key parameters, corresponding to the process of self-organization in the chaos of atoms condensation on the substrate, we use atomic force microscopy, Raman spectroscopy and optical spectrophotometry to study surface morphology, local atomic structure and optical properties of a-C:H films, produced at different synthesis conditions (pressure, discharge power and substrate temperature).
Keywords: ion-plasma sputtering; amorphous carbon films; synthesis conditions; Raman spectra microstructure